2010
DOI: 10.1111/j.1465-3362.2009.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in methamphetamine‐dependent adults 3 years after treatment

Abstract: Introduction and Aims Although psychiatric symptoms are frequently obser ved in methamphetamine (MA) users, little is known about the prevalence of psychiatric disorders in MA-dependent individuals. This is the first study to examine the association of psychiatric disorders with substance use and psychosocial functioning in a large sample of MA users 3 years after treatment. We predicted that psychiatric diagnoses and severity would be associated with substance use and poorer overall functioning over the 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 31 publications
3
73
1
Order By: Relevance
“…Our results are not in line with previous findings suggesting that mental health problems and problematic substance use among dually diagnosed individuals either in psychosocial treatment or in no treatment remain stable or increased over time (Glasner-Edwards et al, 2010;Margolese et al, 2006;Moss et al, 2010). Rather, the results seem to indicate that natural recovery does occur.…”
Section: Discussioncontrasting
confidence: 69%
“…Our results are not in line with previous findings suggesting that mental health problems and problematic substance use among dually diagnosed individuals either in psychosocial treatment or in no treatment remain stable or increased over time (Glasner-Edwards et al, 2010;Margolese et al, 2006;Moss et al, 2010). Rather, the results seem to indicate that natural recovery does occur.…”
Section: Discussioncontrasting
confidence: 69%
“…5 In individuals with substance use disorders, concomitant depression decreases the likelihood of achieving abstinence and predicts more frequent relapses both during and after treatment. 6,7 Studies have shown that among MA-dependent individuals, depressive symptoms tend to be most prominent in early recovery; the risk of relapse is therefore also thought to be particularly high in early recovery.…”
Section: Introductionmentioning
confidence: 99%
“…However the requirements of a treatment trial limit the extent to which the MTP can be used to understand the prevalence or impact of stimulant use disorders in people with serious mental health disorders such as psychoses. Follow up studies of the MTP cohort showed that nearly half of those followed up had significant psychopathology, including significant rates of depression, anxiety, and antisocial personality disorder (Glasner-Edwards et al, 2010b;Glasner-Edwards et al, 2008a;Glasner-Edwards et al, 2009;Glasner-Edwards et al, 2010a). Significant rates of psychotic experiences were also described: at three-year follow up 4.9% had a current psychotic disorder (Glasner-Edwards et al, 2010b) and 13% met criteria for a past psychotic disorder (Glasner-Edwards et al, 2008b).…”
Section: The Overlap Between Cannabis and Stimulant Use Disordersmentioning
confidence: 99%
“…Follow up studies of the MTP cohort showed that nearly half of those followed up had significant psychopathology, including significant rates of depression, anxiety, and antisocial personality disorder (Glasner-Edwards et al, 2010b;Glasner-Edwards et al, 2008a;Glasner-Edwards et al, 2009;Glasner-Edwards et al, 2010a). Significant rates of psychotic experiences were also described: at three-year follow up 4.9% had a current psychotic disorder (Glasner-Edwards et al, 2010b) and 13% met criteria for a past psychotic disorder (Glasner-Edwards et al, 2008b). However, the MTP excluded participants initially meeting DSM-IV criteria for dependence on any other substance (such as alcohol or cannabis) or having other psychiatric conditions requiring immediate care or precluding a focus on treatment of methamphetamine dependence.…”
Section: The Overlap Between Cannabis and Stimulant Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation